Sensitivity and Specificity of the Coma Recovery Scale--Revised Total Score in Detection of Conscious Awareness - Bodien, Yelena G; Carlowicz, Cecilia A; Chatelle, Camille; Giacino, Joseph T (Archives of physical medicine and rehabilitation, 2016)
To describe the sensitivity and specificity of Coma Recovery Scale-Revised (CRS-R) total scores in detecting conscious awareness. Data were retrospectively extracted from the medical records of patients enrolled in a specialized disorders of consciousness (DOC) program. Sensitivity and specificity analyses were completed using CRS-R-derived diagnoses of minimally conscious state (MCS) or emerged from minimally conscious state (EMCS) as the reference standard for conscious awareness and the total CRS-R score as the test criterion. A receiver operating characteristic curve was constructed to demonstrate the optimal CRS-R total cutoff score for maximizing sensitivity and specificity. Specialized DOC program. Patients enrolled in the DOC program (N=252, 157 men; mean age, 49y; mean time from injury, 48d; traumatic etiology, n=127; nontraumatic etiology, n=125; diagnosis of coma or vegetative state, n=70; diagnosis of MCS or EMCS, n=182). Not applicable. Sensitivity and specificity of CRS-R total scores in detecting conscious awareness. A CRS-R total score of 10 or higher yielded a sensitivity of .78 for correct identification of patients in MCS or EMCS, and a specificity of 1.00 for correct identification of patients who did not meet criteria for either of these diagnoses (ie, were diagnosed with vegetative state or coma). The area under the curve in the receiver operating characteristic curve analysis is .98. A total CRS-R score of 10 or higher provides strong evidence of conscious awareness but resulted in a false-negative diagnostic error in 22% of patients who demonstrated conscious awareness based on CRS-R diagnostic criteria. A cutoff score of 8 provides the best balance between sensitivity and specificity, accurately classifying 93% of cases. The optimal total score cutoff will vary depending on the user's objective.